Investigation on the Gas-Phase Decomposition of Trichlorfon by GC-MS and Theoretical Calculation - Jiang, Kezhi; Zhang, Ningwen; Zhang, Hu; Wang, Jianmei; Qian, Mingrong (PLOS ONE, 2015)
The gas phase pyrolysis of trichlorfon was investigated by the on-line gas chromatography – mass spectrometry (GC-MS) pyrolysis and theoretical calculations. Two reaction channels were proposed in the pyrolytic reaction, by analyzing the detected pyrolytic products in the total ion chromatography, including 2,2,2-trichloroacetaldehyde, dimethyl phosphite, and dichlorvos. Theoretical calculations showed that there is an intramolecular hydrogen bond between the hydroxyl group and the phosphate O atom in trichlorfon, through which the hydroxyl H atom can be easily transferred to phosphate O atom to trigger two pyrolytic channels. In path-a, migration of H atom results in direct decomposition of trichlorfon to give 2,2,2-trichloroacetaldehyde and dimethyl phosphite in one step. In path-b, migration of H atom in trichlorfon is combined with formation of the O-P bond to give an intermediate, followed by HCl elimination to afford dichlorvos. Path-a is kinetically more favorable than path-b, which is consistent with the GC-MS results.